Causes and consequences of in-migration: A study of Ratnanagar Municipality, Chitwan (Journal of Innovation in Academia, 2025)
The study focuses on the causes and consequences of in-migration in the context of Ratnanagar Municipality Chitwan. Since fifty years people from hill side have migrated to Ratnanagar municipality. This study basically focuses on why the people from hill and India have migrated to Ratnanagar. The study follows both qualitative and quantitative research designs and asks the questions about the causes to settle down in Ratnanagar that are analyzed on the basis of priorities. Conclusion has been drawn on the basis of analysis and show why they migrated to Ratnanagar and which of the priority plays an important role for those who have migrated from their homelands to the municipality. Searching for jobs and facilities are the major causes to come down in the area. To find out the causes and consequences, questions were asked to fifty individual respondents and analyzed their priorities to migrate in the study area.